COVID-19 and kidney transplantation: the impact of remdesivir on renal function and outcome - a retrospective cohort study. (May 2022) - Elec, Florin; Magnusson, Jesper; Elec, Alina; Muntean, Adriana; Antal, Oana; Moisoiu, Tudor; Cismaru, Cristina; Lupse, Mihaela; Oltean, Mihai
Highlights: Studies on remdesivir as COVID-19 therapy excluded patients with poor renal function Kidney transplant recipients frequently have impaired renal function No negative effect on the renal function was seen after 5 days of remdesivir Remdesivir significantly improved intensive care survival Remdesivir did not seem to reduce overall mortality Abstract: Objectives: The aim of the study was to evaluate the impact of remdesivir on overall mortality, ICU mortality, and renal functional outcome in hospitalized patients with COVID-19 who received kidney transplant. Methods: We reviewed 165 patients with KTx hospitalized owing to COVID-19 between March 1, 2020, and May 31, 2021. A total of 38 patients with KTx received a 5-day RDV treatment, whereas 127 received standard of care (SOC). Overall and ICU mortality along with functional outcome were assessed. Results: The 2 groups had similar baseline characteristics. RDV treatment was completed in all patients without any adverse effects attributable to RDV. In terms of overall mortality, there was no difference between the RDV and SOC groups (18% vs 23%, p >0.05), but the ICU mortality was significantly reduced in the RDV group (39% vs 83%, p <0.05). RDV seems to have no nephrotoxic effect on patients with KTx because there was no difference in the incidence of AKI between RDV and SOC groups (50% vs 43%, p >0.05), and the discharge eGFR values significantly improved in the RDV group compared with the admission values (57 ± 23 vs 44 ± 22, p <0.05). Conclusion: Five-day RDV treatment appears safe in KTx recipients, and without obvious nephrotoxic effects. Also, RDV may decrease ICU mortality attributed to COVID-19.